Effect of Innovation on The Relationship of Knowledge Management Process and Digital Service Performance in UAE Judicial System Model - Katheeri, Hamad Al; Kudus, Norliah (International Journal of Sustainable Construction Engineering and Technology, 2024)
In the UAE's ongoing digital transformation, particularly in the service sector like the Judicial Department, there's a significant gap in understanding the basics of digital innovation, especially in developing countries. Recognizing digital innovation as crucial for government organizations to strengthen their competitive edge by speeding up citizen service, the insufficient exploration of the relationship between knowledge management, digital innovation, and service performance emphasizes the need to bridge this gap for greater efficiency and effectiveness. Hence, this paper reveals a study to establish a mediation model where innovation acts as mediator to the relationship knowledge management processes and digital service performance of the judicial system in UAE. To develop the model, the study adopted quantitative approach where data was collected through questionnaire survey amongst the department’s employees.  The questionnaire was randomly distributed to the selected 332 employees of the department. The collected data was used to develop and assessed the model in SmartPLS software. It was found that the model has achieved all fitness evaluation criteria with GoF value of 0.766 which indicates the model attain large predictive capability. Hypothesis testing found that for direct relationship between knowledge management processes and digital service performance, the relationship is significant having path strength of 0.504. For indirect relationship between knowledge management processes; innovation and digital service performance, it was found that the relationship is significant having a strength of 0.270. Finally, it was found that the innovation is partially mediates the relationship between management construct and digital service performance. The developed model can be applicable in enhancing innovation to improve the relationship of knowledge management process and digital service performance in UAE Judicial System.